Perbedaan Kemampuan Bersosialisasi dan Kematangan Emosional Anak PAUD dan Non PAUD - Dian Afriyanto; Siti Arifah (Jurnal Berita Ilmu Keperawatan, 2018)
Social development is a process of learning to adjust to the morals, traditions, norms and communicate with each other and work together to reach maturity in social relations. Early childhood education (PAUD) is one way to improve a child's development from being obstructed. This study aims to know is there any difference in social skills and emotional maturity in pre-school children with early childhood and without early childhood. This research is a quantitative study with descriptive comparative. The study population was pre-school children totaling 91 children, while the samples are 91 preschoolers with total sampling technique. The results showed the analysis of differences in social skills of preschool children with early childhood and Non early childhood significance value (p-value) 0,014 so H0 rejected and the difference in emotional maturity of preschool children with early childhood and Non early childhood significance value (p-value) 0,000 so H0 rejected. There are any differences in social skills in preschool children with early childhood and non early childhood and there are any differences in emotional maturity in preschool children with early childhood and non early childhood.